Glucose-6-phosphate dehydrogenase deficiency in 2 girls. - Costa, E (1999)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common erythrocyte enzymopathy, affecting over 400 million people worldwide. Portugal is a low prevalence country, but immigrants from endemic regions are common, particularly in the south of the country. In the present study, we report the laboratory findings observed in two black proband children with low G6PD enzyme activity (23 and 18%). The study also included their first-degree relatives. Both biochemical parameters (enzyme activity, electrophoretic mobility and cytochemical test) and genetic determinations (mutation and haplotype characterisation) were performed.